Deployment maturity assessment of product lifecycle management systems: a study in Indian industries. (1st January 2012) - Venugopalan, S.R.; Ganesh, L.S.; Prakash Sai, L.
Product lifecycle management (PLM) is a strategic business approach for enabling innovation, product development, market deployment and disposal. The practice of PLM is comprehensively enabled by product lifecycle management systems (PLMS) that comprise an integrated set of various software products that are blended into organisational policies and practices concerning new product development (NPD). Effective adoption and implementation of PLMS necessarily require their deployment to be assessed for deployment maturity. On a positive note, PLMS deployment maturity has been found to be closely associated with the success rate of NPD projects. This work proposes a 'PLMS deployment maturity assessment framework' that will help organisations assess themselves across different stages of adopting, implementing and evaluating PLM. This work also analysis the deployment maturity of PLMS components of 29 Indian organisations using non-parametric statistical tests. Based on the primary data the work ascertains and estimates the deployment maturity prevailing among the organisations, for the chosen industries. Additionally, this research compares PLMS deployment maturity between three major industries: automotive, aerospace, and hi-tech. We conclude that there exist significant differences between the industries. These results help the organisations to assess themselves on PLMS deployment maturity at each component level.